Reconstructing temporal variation in great ape and other primate diets: A methodological framework for isotope analyses in hair. Issue 10 (3rd November 2015) - Oelze, Vicky M.
Abstract : Stable isotope analysis of carbon and nitrogen in hair provides a versatile tool for reconstructing feeding behavior in elusive primate species. Particularly in great apes, researchers can sample long hair completely non‐invasively from nests, allowing the investigation of inter‐ and intra‐individual dietary variation. Given its incremental growth pattern, hair records temporal shifts in diet over long periods and allows one to reconstruct seasonal dietary patterns in species that cannot be directly observed. However, as for other sample materials, there are potential drawbacks related to the properties of hair keratin. Here I review some important facts on the nature of primate hair and also introduce new isotopic data from infant bonobo hair to provide methodological recommendations for future sample collection in the field and sample preparation in the laboratory. While these methodological guidelines focus on great apes which can be sampled strictly non‐invasively, I also consider applications to other free‐ranging primates. The biochemical composition, growth cycle, isotope turnover rate and isotopic fractionation in hair keratin are particularly relevant for data analysis and interpretation. Also, one can microscopically identify infant hairs and analyze them separately to study nursing and weaning behavior in primates. The goal of this article is to encourage primatologists to analyze the stable isotope ratios of hair to assess primate feeding ecology. Am. J. Primatol. 78:1004–1016, 2016. © 2015 Wiley Periodicals, Inc.